Hydrogeological research in the Machu Picchu Peruvian Antarctic Scientific Station: preliminary results - Ng Cutipa, Wai Long; Masías Alvarez, Pablo Jorge; Ramos Palomino, Domingo A.; Cerpa Cornejo, Luis Moroni; Peña Laureano, Fluquer; Morales Reyna, María del Carmen; Torres Gonzalez, Daniel Enrique (The Scientific Committee on Antarctic Research, 2015)
Machu Picchu Peruvian Antarctic scientific station is a research installation on King George Island, South Shetland Islands (Antarctic Peninsula), was founded in 1988, as temporal scientific base, and it‘s open in austral summer. In January and February 2014, INGEMMET hydrogeological preliminary studies conducted around the Peruvian base to identify an aquifer. Our work was focused to perform a hydrogeological classification of materials by surface mapping, make subsurface explorations (through four piezometers) and take underground and surface water samples, for identify a potential aquifer body. This year during the ANTAR XXIII expedition, we start the Project: ―Hydrogeology of Machu Picchu aquifer, hydroclimatic implications‖. These studies pretend know the characteristics of the aquifer, hydrochemical and isotopic characteristics of groundwater and new prospects for improvement and implementation of the project for the next two years. With the certainty that there is groundwater, we perform the following activities: clean and deeper the old piezometers, install temperature senSørs within these piezometers, and collect water samples. Machu Picchu aquifer is a detrital aquifer. Superficially, it is composed of glacial, alluvial, marine, fluvial, alluvial fluvial and alluvial glacial deposits. Preliminary studies show three horizons. The Horizon 1 (more superficial) consists of cover material with sandy gravel with blocks of different sizes, from 0.05 m in alluvial-fluvial deposits to 1 m in glacial deposits. The Horizon 2 (intermediate) presents silty sandy gravel, silty gravel and sandy silty gravel with thickness of 0.16 m to 0.95 m. The Horizon 3 consists in sandy gravel interbeded with fine levels up to coarse sand lenses, this horizon is wet, saturated and stores groundwater. Our wells have not reached the base level of 3th horizon. In the last expedition groundwater was confirmed in 6 installed piezometers. These level is not static, along the ANTAR XXII expedition level fell between 0.01 and 0.10 m per ...